2021
DOI: 10.21203/rs.3.rs-142984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence and baseline determinants of seropositivity in health care workers up to nine months after COVID-19

Abstract: We determined the duration and baseline determinants of antibody responses to SARS-CoV-2 up to nine months after COVID-19 symptoms onset in 173 primary health care worker patients from Spain. Seropositivity to SARS-CoV-2 spike and RBD antigens was 92.49% (60.69% IgM, 76.3% IgA, 90.17% IgG), with four suspected reinfection cases. Antibody levels significantly correlated with fever, hospitalization, anosmia/hypogeusia, allergies, smoking and occupation, and persisted 149-270 days in this cohort of patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…Around 28% of the total infections detected throughout the follow up were newly diagnosed after the first visit (M0), which would reveal that infections in the hospital setting mostly happened within the first pandemic wave. No re-infections were reported in our cohort and this could be related to the induction and maintenance of robust neutralizing antibodies along the study period, in contrast with another study in a cohort of 173 primary HCW in which 4 reinfections were reported 46 . Surprisingly, only 56% of participants with evidence of infection by serology had a positive rRT-PCR, highlighting that almost half of the infections went under-detected, mainly during the baseline visit (only 49% had a previous positive rRT-PCR) and going up to 73% of rRT-PCR detection rate in the following visits.…”
Section: Discussioncontrasting
confidence: 89%
“…Around 28% of the total infections detected throughout the follow up were newly diagnosed after the first visit (M0), which would reveal that infections in the hospital setting mostly happened within the first pandemic wave. No re-infections were reported in our cohort and this could be related to the induction and maintenance of robust neutralizing antibodies along the study period, in contrast with another study in a cohort of 173 primary HCW in which 4 reinfections were reported 46 . Surprisingly, only 56% of participants with evidence of infection by serology had a positive rRT-PCR, highlighting that almost half of the infections went under-detected, mainly during the baseline visit (only 49% had a previous positive rRT-PCR) and going up to 73% of rRT-PCR detection rate in the following visits.…”
Section: Discussioncontrasting
confidence: 89%
“…Remarkably, compared with our prior analysis post one-year in the same cohort [23], a more steep decay in antibodies was seen after vaccination than following natural exposure, indicating that SARS-CoV-2 infection may induce better memory responses or longer-lived plasma cells.…”
Section: Discussioncontrasting
confidence: 52%
“…We confirmed that individuals with prior history of COVID‐19 still had higher responses almost a year after vaccination, and that post‐vaccination levels were positively associated with pre‐vaccination levels. Remarkably, compared with our prior analysis post one‐year in the same cohort [23], a more steep decay in antibodies was seen after vaccination than following natural exposure, indicating that SARS‐CoV‐2 infection may induce better memory responses or longer‐lived plasma cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Despite the clear impact of SARS-CoV-2 exposure on vaccines responses, time since infection did not have a major effect. In face of shortage of vaccine doses, and based on some studies reporting maintenance of antibody responses in COVID-19 recovered patients for more than 6 months [52][53][54][55] recommendations to wait up to 6-month post-infection to get vaccinated were issued in some countries, including Spain [23]. Nevertheless, at HCB, all HCW were recommended to get the vaccine although naïve individuals were prioritized.…”
Section: Discussionmentioning
confidence: 99%